Interorganizational Influence and Managerial Attitudes - Pfeffer, Jeffrey (Academy of Management Journal, 1972)
Managerial behavior in organizations probably is affected by influences from external organizations in the environment. It is hypothesized that the extent of external influence from specific organizations is related to the degree to which the focal organization is interdependent with the external organization. Data from 141 Israeli managers tend to support the principal hypothesis. Firms that sell relatively more to the government perceive themselves as influenced more by governmental demands; firms that are in relatively poorer financial conditions are influenced more by both the government and banks. Managers tend to report spending more time with external organizations to the extent that the firm is interdependent with them. Also, managers who tend to rank external, government-controlled factors as being more important to organizational success are more likely to rank the importance of having political connections as being more important for a manager.